2016
DOI: 10.1080/01494929.2016.1184211
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Marital Satisfaction in an Emirati Sample: A Structural Equation Model Analysis

Abstract: This study surveyed 1,000 married Emirati men and women to explore a model of marital satisfaction in relation to self-esteem, satisfaction with life, gender-role attitudes and general health (physical and psychological). The Emirati Marital Satisfaction Scale (EMSS; Al-Darmaki et al., were utilized. Confirmatory factor analysis (CFA) on the EMSS indicated a moderate fit of the data to one factor structure. CFA on SSES and SWLS indicated an adequate fit of the data to the four-factor solution and one factor, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
(79 reference statements)
3
4
0
1
Order By: Relevance
“…Overall, the results from the study reveal that marital satisfaction in the UAE is fairly high, suggesting that participants reported having meaningful and fulfilling marital relationships with their spouses. This result is similar to what Al-Darmaki et al (2014) and Al-Darmaki et al (2017) found using samples from the community. However, it is acknowledged that a social desirability effect may be influencing the results, or it may be due to the selection bias in the sample as less satisfied individuals might be less inclined to participate.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Overall, the results from the study reveal that marital satisfaction in the UAE is fairly high, suggesting that participants reported having meaningful and fulfilling marital relationships with their spouses. This result is similar to what Al-Darmaki et al (2014) and Al-Darmaki et al (2017) found using samples from the community. However, it is acknowledged that a social desirability effect may be influencing the results, or it may be due to the selection bias in the sample as less satisfied individuals might be less inclined to participate.…”
Section: Discussionsupporting
confidence: 92%
“…Building on our previous work, this study provides further evidence of the validity and reliability of the EMSS. Similar to previously reported reliabilities (Al-Darmaki et al, 2014; Al-Darmaki et al, 2017), this study revealed high internal consistency for the scale. In addition, the significant correlations observed between EMSS and GF12 and PCAD were in the expected directions and provide additional evidence for the validity of the EMSS and the other two scales.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations